MODEL LEMBAR KEGIATAN SISWA TEKS PROSEDUR DENGAN SIKLUS HAMMOND DI SEKOLAH MENENGAH PERTAMA - Sultan, Sultan; Hamsa, Akmal (Indonesian Journal of Educational Studies, 2015)
This study aims to develop a model of student activity sheet of procedure with the procedure text in Hammond cycles in junior high school. This study was designed using of 4-D which consists of defining phase, designing phase, abd developing phase.Subject were Indonesa learning experts and practioner. The results of rhe development in the form of worksheets that consists of two cycles, the oral cycles and the writing cycles. Each cycles devided into four main activities, which 1) building knowledge ogf text, 2) modeling of text, 3) compose text in group, and 4) compose text independent. Worksheet developed has met the validity criteria.